2022
DOI: 10.1111/iej.13760
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PINK1 and Parkin in human apical periodontitis

Abstract: Aim: PTEN-induced putative kinase 1 (PINK1) and Parkin E3 ubiquitin-protein ligase (Parkin) are critical for immune and inflammatory regulation in health and disease. PINK1 and Parkin have been confirmed to be involved in the progression of apical periodontitis by affecting mitophagy-related osteoblast apoptosis; however, the expression of PINK1 and Parkin in macrophages, one of the most important cells in apical periodontitis, remains unknown. This study aimed to investigate the expression of PINK1 and Parkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…S1P/SK1/S1PR1 signaling might be involved in M2 macrophage polarization induced by ADSC-derived exosomes to improve cardiac damage [35], and pknox1 might participate in M2 macrophage polarization by BMSC-Exos and enhance cutaneous wound healing [36]. PINK1/Parkin signaling is important for macrophage polarization [37]. The activation/phosphorylation of Akt plays a negative role in the PINK1/Parkin signal pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…S1P/SK1/S1PR1 signaling might be involved in M2 macrophage polarization induced by ADSC-derived exosomes to improve cardiac damage [35], and pknox1 might participate in M2 macrophage polarization by BMSC-Exos and enhance cutaneous wound healing [36]. PINK1/Parkin signaling is important for macrophage polarization [37]. The activation/phosphorylation of Akt plays a negative role in the PINK1/Parkin signal pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…Apical periodontitis is primarily derived from complex microbial infections and has identified as a host–immune response against the invasion of microbes in the root canal (Azuma et al, 2018; Liu et al, 2022). Recent studies have suggested that the activation of a glycolytic phenotype is linked to immune responses (Song et al, 2022; Wang, Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of AMPK abolished the effects of FSH on mitophagy, which was reflected in the reduction in TOMM20 expression, the LC3-II/LC3-I ratio, and cellular ATP levels, indicating that AMPK may be a central regulator connecting FSH and mitophagy. LC3 and TOMM20 are typically used as an indicator of autophagic or mitophagic flux, respectively, and the LC3 mitochondrial translocation (LC3 co-localization with TOMM20) represents the formation of mitophagosomes [ 41 ]. AMPK is essential for LC3 lipidation (LC3-I to LC3-II) to induce autophagosome formation, which is consistent with our findings [ 40 ].…”
Section: Discussionmentioning
confidence: 99%